The potential use of augmented reality in gamification - Mohamed Noor, Nurtihah; Yusoff, Fakhrul Hazman; Yussof, Rahmah Lob; Ismail, Marina (2015)
The use of augmented reality (AR) and gamification in various fields is currently gaining popularity for its capability in engaging users.Gamification is a term that defines the use of game-based elements, such as game mechanics, aesthetics, dynamics, and game thinking in the non-game context environment.Meanwhile, AR is a technology that has an ability to overlap computer graphics onto the real environment.However, as a newly emerging concept, gamification seems to have some arguments related to its elements, concepts, and effectiveness in a similar intervention. Therefore, this paper discusses gamification. Although dozens of studies have implemented AR games, there is still an obvious lack in discussing and relating it to a gamified platform. Nevertheless, previous adaptation of games in AR seems that there are also potentials to utilise gamification and AR concepts and elements, as well as AR and AR games in brief.This paper also justifies several previous empirical studies in AR and gamification to look into its elements, research design, and the potentials of AR and gamification combination